2018
DOI: 10.1177/0308022618764781
|View full text |Cite
|
Sign up to set email alerts
|

Adults with intellectual disabilities: Case studies using everyday technology to support daily living skills

Abstract: Introduction: Adults with intellectual developmental disorders may have difficulties undertaking activities of daily living. This study aimed to identify changes in independence in activities of daily living following learning support using individualized everyday technologies. Method: A double-baseline case study design explored the use of everyday technology applications and devices to support functional performance of three men aged 32, 33, and 55 years, with mild to moderate intellectual disabilities. Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…First, eHealth is primarily used as a temporary aid to facilitate training or learning a single daily living skill, a practical skill performed in the community, a vocational skill or a combination of these skills, such as purchasing groceries (e.g., Ayres, Maguire, & McClimon, 2009; Sigafoos et al., 2005). Second, eHealth is used as a permanent support aid in a home situation or vocational context for people with mild intellectual disability themselves, for example to support independent task completion (e.g., Golish, Waldman‐Levi, Swierat, & Toglia, 2018; Van Laarhoven, Johnson, Van Laarhoven‐Myers, Grider, & Grider, 2009). Third, eHealth is used as a facilitator for remote professional support to carry out daily activities, such as video calling to ask for help or remote coaching via a Bluetooth earpiece (e.g., Cavkaytar, Tomris, & Acungil, 2017; Taber‐Doughty, Shurr, Brewer, & Kubik, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, eHealth is primarily used as a temporary aid to facilitate training or learning a single daily living skill, a practical skill performed in the community, a vocational skill or a combination of these skills, such as purchasing groceries (e.g., Ayres, Maguire, & McClimon, 2009; Sigafoos et al., 2005). Second, eHealth is used as a permanent support aid in a home situation or vocational context for people with mild intellectual disability themselves, for example to support independent task completion (e.g., Golish, Waldman‐Levi, Swierat, & Toglia, 2018; Van Laarhoven, Johnson, Van Laarhoven‐Myers, Grider, & Grider, 2009). Third, eHealth is used as a facilitator for remote professional support to carry out daily activities, such as video calling to ask for help or remote coaching via a Bluetooth earpiece (e.g., Cavkaytar, Tomris, & Acungil, 2017; Taber‐Doughty, Shurr, Brewer, & Kubik, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study specifically reported a systematic and methodical approach to determining the needs of participants before starting the intervention with eHealth. That is, Golish et al (2018) used a participant‐centred interview to inventory tasks in which the participants required assistance because they found independent completion difficult. In this study, support staff delivered information on task priorities first, and then, the participant decided which task to target for the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians serving this population may ask themselves whether there are alternative scaffolding techniques that engage individuals with moderate to severe IDD in selecting tasks that are meaningful to them. For example, Golisz, Waldman‐Levi, Swierat and Toglia () describe a procedure where tasks identified by caregivers were presented to adults with mild‐moderate IDD, one at a time. Clients were asked if the task was easy or hard and if they wanted to ‘get better’ at the task (yes or no).…”
Section: Discussionmentioning
confidence: 99%
“…100% of the reviewed studies used target task as the outcome measure, but some also included social validity questionnaires that examined family member perspective (Allen et al) or person's perspective of the intervention (Bouck et al, 2012;Mechling & Seid, 2011). It appears that an observationbased assessment and breakdown of a task to its core elements can be an essential and reliable tool in both research and practice to assess individuals with IDD functional performance (Golisz et al, 2018).…”
Section: Outcome Measuresmentioning
confidence: 99%